Factors influencing students' motivation in online learning for Arabic language courses at UiTM Perlis branch / Ummi Syarah Ismail ... [et al.] - Ismail, Ummi Syarah; Chulan, Majdah; Rosaidi, Nor Alifah; Mohamad Nor, Nor Azriani; Ismail, Noraini; Abdul Pisal, Nadhilah (2021)
Online learning applications are an important medium in Arabic language education to replace face-to-face teaching and learning nowadays. Therefore, this study aims to identify the applications of students' interests in online learning and the factors that influence students' motivation in online learning for Arabic Language courses. This study used a quantitative study design using stratified random sampling. Data were collected using a questionnaire instrument and analyzed using IBM SPSS Statistics software. This questionnaire used the Likert Scale 5 measurement of Strongly Disagree, Disagree, Not Sure, Agree and Strongly Agree to identify the applications that students are interested in online learning and the factors that influence their motivation in online learning for Arabic language courses. The sample involved in the study was a total of 216 students who took Arabic language courses at Universiti Teknologi Mara Perlis. This study suggested that lecturers should use Google Meet, U-Future, WhatsApp, Telegram and Google Classroom applications in teaching Arabic. Meanwhile, the main factors that influenced the student’ motivation in online learning for Arabic language courses are the frequent use of online materials provided as well as the recorded lecture videos.